Pseudodesulfovibrio mercurii sp. nov., a mercury-methylating bacterium isolated from sediment. Issue 3 (11th March 2021) - Gilmour, Cynthia C.; Soren, Ally Bullock; Gionfriddo, Caitlin M.; Podar, Mircea; Wall, Judy D.; Brown, Steven D.; Michener, Joshua K.; Urriza, Maria Soledad Goñi; Elias, Dwayne A.
Abstract : The sulfate-reducing, mercury-methylating strain ND132 T was isolated from the brackish anaerobic bottom sediments of Chesapeake Bay, USA. Capable of high levels of mercury (Hg) methylation, ND132 T has been widely used as a model strain to study the process and to determine the genetic basis of Hg methylation. Originally called Desulfovibrio desulfuricans ND132 T on the basis of an early partial 16S rRNA sequence, the strain has never been formally described. Phylogenetic and physiological traits place this strain within the genus Pseudodesulfovibrio, in the recently reclassified phylum Desulfobacterota (formerly Deltaproteobacteria ). ND132 T is most closely related to Pseudodesulfovibrio hydrargyri BerOc1 T and Pseudodesulfovibrio indicus J2 T . Analysis of average nucleotide identity (ANI) of whole-genome sequences showed roughly 88 % ANI between P. hydrargyri BerOc1 T and ND132 T, and 84 % similarity between ND132 T and P. indicus J2 T . These cut-off scores <95 %, along with a multi-gene phylogenetic analysis of members of the family Desulfovibrionacea, and differences in physiology indicate that all three strains represent separate species. The Gram-stain-negative cells are vibrio-shaped, motile and not sporulated. ND132 T is a salt-tolerant mesophile with optimal growth in the laboratory at 32 °C, 2 % salinity, and pH 7.8. The DNA G+C content of the genomic DNA is 65.2 %. It is an incomplete oxidizer of short chain fatty acids, using lactate, pyruvate and fumarate with sulfate or sulfite as the terminal electron acceptors. ND132 T can respire fumarate using pyruvate as an electron donor. The major fatty acids are iso-C15 : 0, anteiso-C15 : 0, iso-C17 : 0, iso-C17 : 1 ω9 c and anteiso-C17 : 0 . We propose the classification of strain ND132 T (DSM 110689, ATCC TSD-224) as the type strain Pseudodesulfovibrio mercurii sp. nov.